Analisis Penerimaan Pengguna Garda Sumber Pembelajaran Terbuka Indonesia (Garsupati) Menggunakan Model Unified Theory Of Acceptance And Use Of Technology (UTAUT) - Ella Silviasasmi; I Ketut Resika Arthana; I Made Putrama (ULTIMA InfoSys, 2019)
The purpose of this research is to know how the user acceptance to Garsupati system so that system development feasible executed. One approach to the theory of acceptance and use of a technology that is Unified Theory Of Acceptance And Use Of Technology (UTAUT). UTAUT is one of the technology acceptance models developed by Vankatesh, et al. (2003) by combining eight previous technology acceptance theories. UTAUT has four main constructs: 1) performance expectancy, 2) effort expectancy, 3) social influence, and 4) facilitating conditions. This research will further explain about the relation of factors influencing acceptance and usage of Garsupati system using UTAUT model. Data were obtained by distributing questionnaires to students and interviews with lecturers. The sample size in this study amounted to 394 Undiksha students, analyzed using multiple linear regression using SPSS software. The results of this study indicate that (1) performance expectation, business expectation, social factor have positive effect to interest of utilization of Garsupati system (2) facility factor and interest of utilization have positive effect to user behavior. Keywords: OER, Garsupati, UTAUT